2016
DOI: 10.5505/itujfa.2016.82713
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective assessment of environmental and acoustical quality in schools around Istanbul Ataturk International Airport

Abstract: Air traffic noise maps have been drawn for Istanbul Ataturk International Airport. With the establishment of these maps, a study was conducted by using subjective and objective methods in order to assess the noise annoyance levels of students and teachers of schools around airport. Questionnaires and intelligibility tests were designed (with different questions for teachers and students) in order to measure the effect of noise among students and teachers as the classrooms' users. A total of seven hundred and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At the second step of the study, it was observed that the mean NSS value was 88.72 ± 17.97 for 210 volunteers, and 89. 22 (Table 5). Besides, it was observed that 30.48% of all male subjects of the study were in the upper SNS group while it was 26.67% for females (x 2 test, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the second step of the study, it was observed that the mean NSS value was 88.72 ± 17.97 for 210 volunteers, and 89. 22 (Table 5). Besides, it was observed that 30.48% of all male subjects of the study were in the upper SNS group while it was 26.67% for females (x 2 test, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Although the studies presented that environmental high noise appears to be important problem in Turkey [22][23][24] and there are some noise-annoyance questionnaires adapted to Turkish [23,25] and developed in Turkish [24], noise sensitivity has never been subject to any research in the Turkish population as much as we found in the English and Turkish literature. For the measurement of SNS, long and short questionnaires have been proposed [7]; the Weinstein noise sensitivity scale (WNSS) has been one of the most widely used standard questionnaires with high validity, reliability, and internal consistency [3,4,26,27].…”
Section: Introductionmentioning
confidence: 96%
“…The materials applied in the software were first validated by a study that measured reverberation time and speech intelligibility in a refurbished classroom with the same floor, walls, windows and suspended ceiling finishing materials in Istanbul. 64 The design guide 42 recommended the use of suspended ceilings with at least 0.75 weighted sound absorption coefficient, α w .…”
Section: Methodsmentioning
confidence: 99%